ATTENUATION OF HAEMODYNAMIC RESPONSE TO LARYNGOSCOPY AND ORAL ENDOTRACHEAL INTUBATION IN CORONARY ARTERY BYPASS SURGERY PATIENTS: INTRAVENOUS MORPHINE AND LIDOCAINE VERSUS INTRAVENOUS MORPHINE AND LIDOCAINE SPRAY - Islam, Mujahid Ul; Ahmad, Imtiaz; Shah, Azmat Ali; Islam, Ansa (Journal of Ayub Medical College Abbottabad, 2014)
Background: Sympathetic response associated with laryngoscopy and endotracheal intubation is recognized as a potential cause for a number of complications especially in coronary bypass surgery patients. Various methods have been used to attenuate these hemodynamic responses, The aim of our study was to compare lidocaine spray in addition to intravenous morphine on attenuating the hemodynamic response to laryngoscopy and endotracheal intubation with intravenous lidocaine and morphine in coronary artery bypass surgery patients. Method: Sixty patients, scheduled for elective coronary bypass grafting surgery were included in this randomized controlled trial. The patients randomly divided in group-A (Intravenous Morphine 0.1mg/kg and Intravenous lidocaine 1.5 mg/kg) and group-B (Intravenous Morphine 0.1mg/kg and lidocaine spray 1.5 mg/kg). Results: Demographic data was comparable in both groups. There was no statistically significant difference between two groups in the duration of laryngoscopy and intubation. There was statistically insignificant attenuation in heart rate in both groups (p=0.134), the trends of attenuation of systolic blood pressure, diastolic blood pressure and mean arterial pressure in group-A compared to group-B (p=0.933), (p=0.768) and (p=0.136) respectively were statistically insignificant. Conclusions: Under the present study design, lidocaine spray in addition to intravenous morphine had no better effect on attenuating the hemodynamic response to laryngoscopy and endotracheal intubation as compared to intravenous lidocaine and morphine in coronary artery bypass surgery patients. Keywords: Lidocaine, Hemodynamic response, laryngoscopy, endotracheal intubation, coronary bypass grafting